Transformation of Circular Polarization Along the Propagation Axis via a Polarization-Mixed Metasurface - Changhyun Lee; Jun Seok Yoon; Hyeon Woo Jeon; Seokjae Yoo; Soo Jin Kim (IEEE Access, 2025)
Polarization is a fundamental property of light and plays an important role in a wide range of optical phenomena and applications. While many earlier studies of metasurfaces have primarily focused on controlling polarization within the transverse plane, recent research has extended to explore the control along the light propagation direction. In this study, we design and analyze a Bessel beam–based metasurface capable of continuously varying the circular polarization state of light along its propagation axis. By leveraging polarization beating arising from the spatially engineered superposition of four circularly polarized (CP) components with distinct spatial frequencies, the proposed metasurface enables continuous switching between left-handed circular polarization (LCP) and right-handed circular polarization (RCP) along the propagation axis, which remains robust regardless of the orientations of incident linear polarization. We further demonstrate such metasurfaces being compatible with beams carrying orbital angular momentum (OAM). This dynamic polarization-switching capability offers precise and flexible control of polarization states, paving the way for the potential applications including optical communication, 3D imaging, and chiral sensing.